2021
DOI: 10.1186/s13031-021-00338-9
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study on health care providers’ experiences of providing comprehensive abortion care in Cox’s Bazar, Bangladesh

Abstract: Background Humanitarian settings are characterised by limited access to comprehensive abortion care. At the same time, humanitarian settings can increase the vulnerability of women and girls to unintended pregnancies and unsafe abortions. Humanitarian actors and health care providers can play important roles in ensuring the availability and accessibility of abortion-related care. This study explores health care providers’ perceptions and experiences of providing comprehensive abortion care in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…A total of 15 studies were included in this review from four countries: Bangladesh (5), Pakistan (5), Iran (4), and Malaysia (1), focusing on the SRH of the Rohingya and Afghan refugees. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Most studies exclusively focused on women of reproductive age; only one study focused on both men and women. One study reported the maternal mortality among Afghan refugees in Pakistan before and after an intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 15 studies were included in this review from four countries: Bangladesh (5), Pakistan (5), Iran (4), and Malaysia (1), focusing on the SRH of the Rohingya and Afghan refugees. [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] Most studies exclusively focused on women of reproductive age; only one study focused on both men and women. One study reported the maternal mortality among Afghan refugees in Pakistan before and after an intervention.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…[34,37] Therefore, social norms, stigma, cultural values, and barriers to health-care limit their access to SRH services and influence their needs, knowledge, and perceptions regarding SRH. [43] Implementation strategies to uptake family planning and maternal, new-born, and child health…”
Section: -41mentioning
confidence: 99%
“…For example, healthcare professionals "have been found to impose conditions on SRH [sexual reproductive health] care that are not stated in the national… [menstrual regulation] guidelines, such as having a husband's permission." 20 The refugee healthcare community could do more to mitigate the potential of retribution taken by male community members against women that accept care by dispelling common misconceptions and precluding male community members from influencing female reproductive choices. 21 However, some current practices allow the infiltration of male community leaders and husbands into the diagnosis, decision-making, and treatment spaces.…”
Section: Beneficence In Providing Care To Refugeesmentioning
confidence: 99%
“…While both countries have seen reductions in their maternal mortality rates since the creation of the Millennium Development Goals, neither is currently on track to achieve the reduction in rates aimed for in SDG 3 [ 26 ]. Achieving the SDGs will require improving the provision of comprehensive abortion care (including safe abortion care, post-abortion care and contraceptive counseling) [ 1 , 27 ]. Further, ensuring women have access to reproductive health care in a way that is contextually resonant and rooted in their desires, needs and priorities is imperative for attaining reproductive justice .…”
Section: Introductionmentioning
confidence: 99%